2002
DOI: 10.1038/sj.onc.1205069
|View full text |Cite
|
Sign up to set email alerts
|

A conserved intronic response element mediates direct p53-dependent transcriptional activation of both the human and murine bax genes

Abstract: Both the human and the mouse bax promoters contain p53 binding sites which are su cient to confer p53-dependent transcriptional activation in a heterologous setting. Nevertheless in the context of the bax promoter, these sites do not mediate a p53-dependent response, suggesting that bax may not be a direct transcriptional target of p53. Here, data are presented identifying a conserved p53 response element in the ®rst intron of both the human and the murine bax genes. This element both in isolation and in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 27 publications
1
79
1
Order By: Relevance
“…The 21 kDa protein partner Bax, which overexpresses to counter the death repressor activity of Bcl-2, can enhance apoptosis. The ratio of Bcl-2 to Bax determines survival or death following an apoptotic stimulus [23][24] In this study, the combination subsequently increased Bax and decreased Bcl-2 expression resulting from p53 upregulation. The wild-type p53 gene is a negative regulator of cell growth by the transcriptional activation of p21 which plays a crucial role in controlling DNA repair, cell differentiation, and apoptosis in response to p53 activation [25] .…”
Section: Discussionmentioning
confidence: 97%
“…The 21 kDa protein partner Bax, which overexpresses to counter the death repressor activity of Bcl-2, can enhance apoptosis. The ratio of Bcl-2 to Bax determines survival or death following an apoptotic stimulus [23][24] In this study, the combination subsequently increased Bax and decreased Bcl-2 expression resulting from p53 upregulation. The wild-type p53 gene is a negative regulator of cell growth by the transcriptional activation of p21 which plays a crucial role in controlling DNA repair, cell differentiation, and apoptosis in response to p53 activation [25] .…”
Section: Discussionmentioning
confidence: 97%
“…ZNF659 and LRRC3B were both associated with 10 μmol/l cisplatin, whereas PITX2 and LARP2 were associated with 2.5 μmol/l (PITX2), 5 μmol/l (LARP2), and 20 μmol/l (PITX2) cisplatin. Particular attention may be paid to conserved intronic SNPs within LRRC3B (rs7652737) and PITX2 (rs17624452), which may provide enhancer binding sites or response elements for other genes [51]. Some of the associated nongenic SNPs are found in conserved regions of the genome.…”
Section: Discussionmentioning
confidence: 99%
“…S7B); this suggests that DEC1 inhibits Bax expression through another mechanism. Previous reports showed that the Bax promoter contains four E-boxes downstream of four p53-half sites (32) and a p53-RE in intron 1 (33) (Fig. S7A).…”
Section: Dec1mentioning
confidence: 99%